KOMPARATIF PENDAPATAN PETAMBAK GARAM RAKYAT TEKNIK PRODUKSI PEREBUSAN DENGAN TEKNIK PRODUKSI LADANG DI DESA SEKOTONG BARAT KECAMATAN SEKOTONG KABUPATEN LOMBOK BARAT - Ulil Amri (Fakultas Pertanian Universitas Mataram, 2018)
The purpose of this research are (1) Comparison of income between folk salt farmers who use techniques boiling production and who use techniques agricultural field production; (2) identifying the constraints which is faced by farmers in producing folk salt; and (3) Identifying of the factors that affect the income of farmers and analyzing the influence of these factors on the income salt farmers in West Sekotong village. The results of this research indicate that (1) There is a real difference between income of salt farmers who use techniques boiling production with income of salt farmers who use techniques agricultural field production; (2) Constraints that are faced by salt farmers who use techniques boiling production are firewood and weather. Whereas the constraints that are faced by salt farmers who use techniques agricultural field production are the prices, weather and land limitedness; and (3) The factors which affect the amount of income that would be received by the salt farmers is the day of the employment and experience.